Penguatan Karakter Siswa Melalui Mata Pelajaran Sejarah Kebudayaan Islam Kelas IV MI Ma’arif Gondang Watumalang Tahun Pelajaran 2023/2024 - Maisaroh Setia Hendriani; Sri Haryanto; Salis Irvan Fuadi (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
This research aims to find out how character strengthening is carried out by teachers through Islamic cultural history subjects in class IV, to find out what obstacles teachers have in the process of learning Islamic cultural history, and to find out what the results of strengthening or forming students' character through subjects are. history of Islamic culture class IV MI Ma'Arif Gondang Watumalang. This research is descriptive field research. The data collection techniques used include participant observation, interviews and documentation. The results of the research show that strengthening students' character carried out by teachers of Islamic cultural history subjects in class IV is considered appropriate, because through Islamic cultural history subjects students can know the personality of the Prophet Muhammad, the history of Islamic figures, and students' character can be formed and applied in life. everyday, then the obstacles experienced by teachers are the different backgrounds of students, so that in delivering and applying the material not all students can immediately accept it, strengthening student character carried out by teachers through Islamic cultural history subjects can be said to be successful, because Islamic cultural history subjects are subjects that greatly contribute to the formation and strengthening of students' character.